The Effect of Sharia Financial Literacy and Risk Perception on the Intention to Use Shopee Paylater in Generation Z with Religiosity as a Moderating Variable (A Study on UIN Alauddin Makassar Students) - Nurhidayah Nurhidayah; Saiful Muchlis; Nasrullah Bin Sapa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Sharia financial literacy and risk perception on the intention to use Shopee PayLater among Generation Z students at UIN Alauddin Makassar, as well as to evaluate the role of religiosity as a moderating variable in this relationship. A quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method was employed. The sample consisted of 210 respondents, determined based on Hair’s conservative sample size approach. Data were collected through a questionnaire covering the variables of Sharia financial literacy, risk perception, intention to use, and religiosity. The results showed that Sharia financial literacy had no significant effect on the intention to use Shopee PayLater. In contrast, risk perception had a significant negative effect, indicating that the higher the risk perception, the lower the intention to use the service. The interaction between religiosity and Sharia financial literacy, as well as between religiosity and risk perception, did not show a significant moderating effect on the intention to use Shopee PayLater. Therefore, religiosity does not moderate the relationship between Sharia financial literacy or risk perception and the intention to use Shopee PayLater. This study provides theoretical contributions to the development and deeper understanding of Sharia financial literacy, risk perception, intention to use, and religiosity in the context of using PayLater-based digital financial services.